2014
DOI: 10.3390/ijms151017478
|View full text |Cite
|
Sign up to set email alerts
|

Association of CDKN2BAS Polymorphism rs4977574 with Coronary Heart Disease: A Case-Control Study and a Meta-Analysis

Abstract: The goal of our study was to explore the significant association between a non-protein coding single nucleotide polymorphism (SNP) rs4977574 of CDKN2BAS gene and coronary heart disease (CHD). A total of 590 CHD cases and 482 non-CHD controls were involved in the present association study. A strong association of rs4977574 with CHD was observed in females (genotype: p = 0.002; allele: p = 0.002, odd ratio (OR) = 1.57, 95% confidential interval (CI) = 1.18–2.08). Moreover, rs4977574 was more likely to be a risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…An 11‐year follow‐up study including 925 patients with CHD and 634 without CHD showed that the G allele of rs4977574 (OR = 1.47, P = .003), located in the ANRIL gene locus, was associated with CHD but could not predict cardiovascular mortality (HR = 1.25, based on regression analysis) . Huang et al enrolled 590 CHD and 482 non‐CHD patients in a case‐control study and found that the ANRIL SNP (rs4977574) was closely associated with CHD (OR: 1.57, P = .002) . Samaneh et al demonstrated in a cohort study, which enrolled 420 patients with CHD from the population of the Tehran lipid and glucose study (TLGS) and matched 407 healthy controls with age and sex, that the presence of risk alleles of an ANRIL SNP (rs7865618) was associated with CHD ( P = .03; OR: 1.73; CI 95%: 1.04‐2.88) .…”
Section: Resultsmentioning
confidence: 99%
“…An 11‐year follow‐up study including 925 patients with CHD and 634 without CHD showed that the G allele of rs4977574 (OR = 1.47, P = .003), located in the ANRIL gene locus, was associated with CHD but could not predict cardiovascular mortality (HR = 1.25, based on regression analysis) . Huang et al enrolled 590 CHD and 482 non‐CHD patients in a case‐control study and found that the ANRIL SNP (rs4977574) was closely associated with CHD (OR: 1.57, P = .002) . Samaneh et al demonstrated in a cohort study, which enrolled 420 patients with CHD from the population of the Tehran lipid and glucose study (TLGS) and matched 407 healthy controls with age and sex, that the presence of risk alleles of an ANRIL SNP (rs7865618) was associated with CHD ( P = .03; OR: 1.73; CI 95%: 1.04‐2.88) .…”
Section: Resultsmentioning
confidence: 99%
“…The CDKN2A and CDKN2B genes were shown to be significantly associated with an increased risk of CAD (21%) [ 3 , 4 , 11 ]. Several studies have identified a significant association of specific SNPs in the 9p21.3 locus with CAD [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, the majority of these studies were primarily conducted on Caucasian, African American, and Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analysis by successive omission of individual studies to examine the stability of the pooled ORs, revealed a significant change when the data reported by Tang et al, Huang et al, Sakalar et al or Sehime et al was removed (Supplementary Figure 1A–D). [ 16 19 ] Publication bias was detected by funnel plot. The symmetric funnel plot presented no significant publication bias in this meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al previously conducted a meta-analysis assessing the association between ANRIL polymorphisms and CAD risk. [ 19 ] However, the literature search was performed before 2012, with few data sets combined. A lot more case–control studies on this topic emerged since then, with 9 more studies eligible by the literature search until July 2019.…”
Section: Discussionmentioning
confidence: 99%